Practice profile of Indian gynaecologists on the use of micronized progesterone and dydrogesterone in pregnancy and assisted reproductive technology cycles: progress survey - Ingale, Kundan; Malhotra, Neharika; Deshmukh, Priyanka; Dhonde, Devika; Mehta, Sucheta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Though progesterone supplements are prescribed for progesterone deficiency in pregnant and infertile women, there is ambiguity on the different forms of progesterone supplements prescribed in various conditions, duration, dosing regimen, etc. The aim of this survey was to gain insights into the practice profile of Indian Gynaecologists on progesterone supplements and the various factors governing these choices. Methods: A total of 513 practicing gynecologists completed a digital survey on usage patterns of Micronized progesterone (NMP) and Dydrogesterone (DYD) in pregnancy and Assisted Reproductive Technology (ART) cycles. Data were analyzed using suitable statistical tests. Results: A total 48% and 41.9% prescribed DYD and NMP-sustained release (NMP-SR) in 20-50% patients respectively, and 58.5% prescribed NMP capsule in <20% patients. >50% gynaecologists prefer DYD as progesterone supplements for threatened abortion (TA), preterm birth (PTB), Recurrent abortion (RA), and luteal phase support (LPS) in ART. Patient’s obstetrics history (26.2%), indication (18.6%), and route of administration / efficacy (12.2% each) were the top factors considered for prescribing progesterone supplements. 67.8% gynaecologists prescribe multiple progesterone preparations and of these 38.7% combined DYD + NMP-SR. 35.8% gynaecologists prefer DYD 10 mg thrice daily to prevent preterm labour in case of twin pregnancy, and 43.5% gynaecologists reported prescribing DYD 40 mg immediately followed by 30mg/day for 7 days in TA. Conclusions: This survey provided insights into usage patterns of oral and vaginal Progesterone preparations in PTB, TA, RA and LPS in ART. DYD emerged as a crucial component in the realm of pregnancy care.